Phytochemical Screening, Antioxidant and Antimicrobial Activity of the Ethanolic leaf Extract of Tinospora crispa (L.) Miers [Menispermaceae] - Shree, J Akila; Krishnaveni, C (Asian Journal of Biological and Life Sciences)
The qualitative phytochemical analysis showed the presence of alkaloids, glycosides, flavonoids, tannins and phenols in the ethanol leaf extracts. The ethanol leaf extract showed highest tannin, phenol and flavonoid content that the other extracts such as hexane and water in the phytochemical analysis. In vitro antioxidant analysis showed that the ethanol leaf extract shows moderately good free radical scavenging activity when compared with standard Ascorbic acid. The in vitro antimicrobial analysis showed good zone of inhibition against most of the tested microorganisms in the concentration dependent manner. The present study showed that the ethanol extract of Tinospora crispa leaves has significant number of phytochemicals, antioxidant and antimicrobial activity. Many biologically active secondary metabolites were present in the leaf extract which could be responsible for its therapeutic potential.
Keywords: Anti-microbial; Antioxidant; Ethanolic leaf extract; Ethnomedicinal plant.; Tinospora crispa